FUNDAMENTALS OF THERMAL-FLUID SCIENCES - Çengel, Yunus A.; Cimbala, John M.; Ghajar, Afshin J. (McGraw Hill, LLC, 2022)
Fundamentals of Thermal-Fluid Sciences, Sixth Edition, is an abbreviated version of standard thermodynamics, fluid mechanics, and heat transfer texts, covering topics that the majority of engineering students will need in their professional lives. The text is well-suited for curriculums that have a common introductory course or a two-course sequence on thermal-fluid sciences. The book addresses tomorrow's engineers in a simple, yet precise manner, and it leads students toward a clear understanding and firm grasp of the basic principles of thermal-fluid sciences. Special effort has been made to appeal to readers' natural curiosity and to help students explore the various facets of the exciting subject area of thermal-fluid sciences.